Spatialising time: Perceiving multiple layers of time in narrative environment - Kezia Nathania; Arif Rahman Wahid (Department of Architecture Faculty of Engineering Universitas Indonesia, 2022)
There is no escape from time. That includes architecture which dominantly discusses space. This paper aims to explore how people can experience time spatially. Notably, this study looks at the context of the narrative environment where stories are imbued in space to enhance their engagement with the audience. Time in a narrative is presented through the narrated time and the real-world time where the audience of the narrative perceive it. Both types of time can be overlapped, whether the audience is consciously aware of that or not. Time is integrated into a narrative through order, plot, pace, and duration. All these four aspects are experienced by the visitor of a narrative environment to connect events and make sense of their journey and the whole story. The relationship between events experienced through time creates a spatial trajectory. Two case studies were conducted to explore this idea: a visit to Museum Kebangkitan Nasional and participation in Secret Cinema. It is found that time can be spatialised through the explicit transition of graphics, a play of lighting, and overall spatial organisation.